An Analysis Framework for Electronic Health Record Systems - Bisbal, J.; Berry, D. (Methods of Information in Medicine, 2011)
Background: The timely provision of complete and up-to-date patient data to clinicians has for decades been one of the most pressing objectives to be fulfilled by information technology in the healthcare domain. The so-called electronic health record (EHR), which provides a unified view of all relevant clinical data, has received much attention in this context from both research and industry. This situation has given rise to a large number of research projects and commercial products that aim to address this challenge. Different projects and initiatives have attempted to address this challenge from various points of view, which are not easily comparable.Objectives: This paper aims to clarify the challenges, concepts, and approaches involved, which is essential in order to consistently compare existing solutions and objectively assess progress in the field.Methods: This is achieved by two different means. Firstly, the paper will identify the most significant issues that differentiate the points of view and intended scope of existing approaches. As a result, a framework for analysis of EHR systems will be produced. Secondly, the most representative EHR-related projects and initiatives will be described and compared within the context of this framework.Results: The main result of the present paper is an analysis framework for EHR systems. This is intended as an initial step towards an attempt to structure research on this field, clearly lacking sound principles to evaluate and compare results, and ultimately focusing its efforts and being able to objectively evaluate scientific progress.Conclusions: Evaluation and comparison of results in medical informatics, and specifically EHR systems, must address technical and nontechnical aspects. It is challenging to condensate in a single framework all potential views of such a field, and any chosen approach is bound to have its limitations. That being said, any well structured comparison approach, such as the framework presented here, is better than no comparison framework at all, as has been the current situation to date. This paper has presented the first attempt known to the authors to define such a framework.
Keywords: Electronic health records; analysis; comparison; framework; two-level modeling; archetypes; integration; interoperability; semantic interoperability